An Empirical Analysis Of The Effect Of Stock Diversification on Portfolio Risk Optimization: Evidence From The Nepalese Share Market - Magar, Raju Rana; B.K, Ganesh Bahadur (Journal of Advanced Academic Research, 2025)
Diversification refers to investments made in a variety of sectors. It is designed to make the portfolio more efficient and optimize return while minimizing risk. Diversification is an investment approach that allocates funds across various assets, thereby reducing risk and enhancing portfolio returns. By diversifying the variety of assets in a portfolio, it is possible to achieve a rational trade-off for investment gain and practical risk reduction. This study aims to empirically examine the impact of selected stock diversification on portfolio risk and return in the Nepalese share market using diversification as a key parameter to identify an optimal portfolio. The study provides a better strategy for fund managers, individual investors, and Mutual funds investment companies, etc. Markowitz’s Diversification model is applied to evaluate portfolio effectiveness using available historical data from the Nepal Stock Exchange website. Data assessment indicates that a diversified portfolio, comprising different sectors, yields a higher return than a single-sector portfolio. Specifically, Portfolio 2, which is diversified in stocks, yields a better return than Portfolio 1. Based on these observations, we can conclude that stock market diversification serves as a risk-reducing cushion, supporting the maximization of returns over a specified period. These findings suggest that stock diversification serves as a hedge for investors in downturns.